Re-evolution of Durum Wheat by Introducing the Hardness and Glu-D1 Loci - Morris, Craig F.; Kiszonas, Alecia M.; Murray, Jessica; Boehm, Jeff; Ibba, Maria Itria; Zhang, Mingyi; Cai, Xiwen (Frontiers in Sustainable Food Systems, 2019)
Durum wheat is an important crop worldwide. In many areas, durum wheat appears to have competitive yield, and biotic and abiotic advantages over bread wheat. What limits durum production? In one respect, the comparatively more limited processing and food functionality. Two traits directly relate to these limitations: kernel texture (hardness) and gluten strength. We have addressed both using ph1b-mediated translocations from bread wheat. For kernel texture, ca. 28 Mbp of chromosome 5D short arm replaced about 20 Mbp of 5B short arm. Single Kernel Characterization System (SKCS) hardness was reduced from ca. 80 to 20 as the puroindolines were expressed and softened the endosperm. Break flour yields increased from 17 to >40%. Straight-grade flour had low starch damage (2%), and a mean particle size of 75 μm. Crosses with CIMMYT durum lines all produced soft kernel progeny and a high degree of genetic variance for milling and baking quality. Solvent Retention Capacities (SRC) and cookie diameters were similar to soft white hexaploid wheat, showing that soft durum can be considered a “tetraploid soft white spring wheat.” Regarding gluten strength, CIMMYT durums contributed a high genetic variance, with the “best” progeny exhibiting Na-dodecylsulfate (SDS) sedimentation volume, SRC Lactic Acid and Mixograph characteristics that were similar to medium-gluten-strength U.S. hard red winter. The best loaf volume among these progeny was 846 cm3 at ca. 12.8% flour protein. To further address the issue of gluten strength, Soft Svevo was crossed with durum lines possessing Dx2+Dy12 and Dx5+Dy10. Bread baking showed that Dx5+Dy10 was overly strong, whereas Dx2+Dy12 significantly improved bread loaf volume. The best progeny produced a loaf volume of 1,010 cm3 at 12.1% protein. As a comparison, the long-term in-house regression for loaf volume-flour protein for hard “bread” wheats is 926 cm3 at 12.1% protein. Obviously, from these results, excellent bread making potential has been achieved.